The American Jewish philanthropic complex : the history of a multibillion-dollar institution - Berman, Lila Corwin, 1976- (Princeton University Press, 2020)
"Acts of charity are at the heart of most traditions of Jewish collective life. It is not surprising, then, that as Jewish immigrants established strong communities in the United States in the course of the last century, philanthropy offered them a pathway to effective communal self-help as well as political and economic power and influence. Partaking in American traditions of associational life, volunteerism, and decentralized religious organization, Jews in the U.S. established philanthropic organizations that have grown to be vital forces in Jewish public life. This book charts the history of American Jewish philanthropic practices and institutions from the late nineteenth-century to the present day. This book offers a nuanced assessment of contemporary American Jewish philanthropy. On the one hand, Berman readily acknowledges that this world of charitable giving is filled with well-intentioned people whose institutional donations have provided invaluable support for many worthwhile projects and causes. (The author herself notes early in the book her own reliance, at key moments in her professional career, on Jewish philanthropy.) On the other hand, these good intentions and good works coexist with a vast accumulation of wealth within Jewish philanthropic organizations that, for Berman, exacerbate rather than alleviate worrisome social and economic inequalities in the U.S"--